(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study determined the relationship between knowledge dissemination, learning self-efficacy and task performance of business educators in tertiary institutions in South-south Nigeria. A correlational survey design was adopted. The study population was 137 business educators from universities in South-South Nigeria, which also made up the sample size. The instrument used for data collected was a questionnaire which was face validated by three experts. Its reliability was measured using Cronbach alpha method and an overall alpha value of 0.892 was obtained. Data collected were analyzed using, mean, standard deviation and regression with bias corrected bootstrap. The study found that knowledge dissemination does not predict learning self-efficacy of business educators. However, knowledge dissemination and learning self-efficacy separately predict task performance of business educators in South-South universities in Nigeria. Based on the findings it was recommended that, universities management should encourage knowledge dissemination as this will lead to high task performance of business educators in institutions, and business educators should make effort to improve on themselves by attending academic workshops and seminars as this will make them efficacious and optimally enhance their task performance.